A review of cryptocurrencies research. (28th June 2022) - Sarpong, Maame Akua
Crypto currencies research is seen as young field though has made drastic impact with the introduction of Bitcoin. In order to strengthen the relatively young multidisciplinary field, there is a need to conduct review of literature. Therefore, it is deemed opportune to carry out systematic literature review which could unveil gaps for future studies and also inform policy makers in preparation towards adoption of cryptocurrencies. About 22 articles were filtered from sampled 42 articles after critically examining them on basis of contribution of insights drawn for discussion based on the model adopted for thematic analysis. The four-step life cycle model comprise of: needs assessment, design, adoption issues and impact assessment. Alternative coins have emerged which calls for comparative analysis and review to explore its usage. User perception of the crypto markets and the likelihood of governments deploring its use are areas considerable of further studies.